2021
DOI: 10.14233/ajchem.2021.23374
|View full text |Cite
|
Sign up to set email alerts
|

Grain Processing Methods’ Effectiveness to Eliminate Mycotoxins: An Overview

Abstract: Mycotoxins like aflatoxins, ochratoxins, patulin, citrinin, deoxynivalenol (DON), fumonisins, trichothecenes, etc., produced by molds (Aspergillus avus, A. parasiticus, Penicillin spp, etc.) could occupy such grains as peanuts, millet, sunower, cassava, beans, sesame, sorghum, maize, etc. In order to either eliminate and or reduce the levels of mycotoxins, as well as detection limits, there are a number of grain processing techniques that have been reported in the literature. In this article, an overview of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Navale et al (2021) described the studies done on AFB 1 , which mostly focused on evaluating its teratogenic effects on chicks, rats, chickens, and eggs, and found teratogenic activities. Mohamed et al (2022) Due to the persistence of mycotoxins such as AFB 1 and AFG 1 , in foods and feeds, many other studies have been done recently with the aim of harnessing novel ways to control these biological toxins (Awuchi, Ondari, Ofoedu, et al, 2021;Chinaza et al, 2021). The effectiveness of the method developed in this study demonstrates comparative advantage, including cost-effectiveness, in removing mycotoxins compared with many methods that have been used in previous studies.…”
Section: Ta B L Ementioning
confidence: 99%
See 2 more Smart Citations
“…Navale et al (2021) described the studies done on AFB 1 , which mostly focused on evaluating its teratogenic effects on chicks, rats, chickens, and eggs, and found teratogenic activities. Mohamed et al (2022) Due to the persistence of mycotoxins such as AFB 1 and AFG 1 , in foods and feeds, many other studies have been done recently with the aim of harnessing novel ways to control these biological toxins (Awuchi, Ondari, Ofoedu, et al, 2021;Chinaza et al, 2021). The effectiveness of the method developed in this study demonstrates comparative advantage, including cost-effectiveness, in removing mycotoxins compared with many methods that have been used in previous studies.…”
Section: Ta B L Ementioning
confidence: 99%
“…Many industrial and domestic processes, including heat treatment (roasting, boiling, and frying), fermentation, and irradiation, among others, have been studied for the removal of mycotoxins in foods (Awuchi, Ondari, Ofoedu, et al, 2021;Ozkan et al, 2023). However, most of these studies reported incomplete or insufficient elimination of these mycotoxins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IARC classifies fumonisins as Group 2B, i.e., possibly carcinogenic to humans (refer to Table 3 ). In general, mycotoxin removal from foods and feeds has some challenges, which means that their presence is a serious health concern [ 206 ]. Trichothecenes have been shown to have multiple inhibitory activities on eukaryotes by inhibiting DNA synthesis, mitochondrial function, RNA synthesis, and protein synthesis, as well as by affecting cell membrane and cell division [ 207 , 208 ].…”
Section: Actions Of Mycotoxins On Human Cellular Genome: a Primermentioning
confidence: 99%
“…Mycotoxin reduction could result from food processing operations, such as extrusion, which can simultaneously improve product quality and increase food safety levels by reducing toxins [ 103 ]. Conventional cooking treatments (conducted at temperatures below 100 °C) cannot participate in the mitigation of mycotoxins in food products because most of these toxins are heat stable.…”
Section: Single Detoxification Treatments Used In Solid Foods and Feedsmentioning
confidence: 99%